Peningkatan Keterampilan Kelompok Julu Atia melalui Pelatihan Pembuatan Nugget Rumput Laut - Kasmiati, Kasmiati; Andriani, Irma; Massi, Muh. Nasrum; Rahmi, Rahmi; Anas, Lukman; Zakiyabarsi, Furqan (Universitas Nusantara PGRI Kediri, 2026)
Seaweed is a leading commodity in the fisheries sector that has not been optimally utilized, particularly by community groups, to increase its added value. The problem faced by these groups is a lack of knowledge and skills in processing and selling seaweed-based products. This activity aims to improve the knowledge and skills of